Preventing antiblastic drug-related cardiomyopathy: old and new therapeutic strategies. (May 2016) - Cadeddu, Christian; Mercurio, Valentina; Spallarossa, Paolo; Nodari, Savina; Triggiani, Marco; Monte, Ines; Piras, Roberta; Madonna, Rosalinda; Pagliaro, Pasquale; Tocchetti, Carlo G.; Mercuro, Giuseppe
Abstract : Because of the recent advances in chemotherapeutic protocols, cancer survival has improved significantly, although cardiovascular disease has become a major cause of morbidity and mortality among cancer survivors: in addition to the well-known cardiotoxicity (CTX) from anthracyclines, biologic drugs that target molecules that are active in cancer biology also interfere with cardiovascular homeostasis. Pharmacological and non-pharmacological strategies to protect the cardiovascular structure and function are the best approaches to reducing the prevalence of cardiomyopathy linked to anticancer drugs. Extensive efforts have been devoted to identifying and testing strategies to achieve this end, but little consensus has been reached on a common and shared operability. Timing, dose and mode of chemotherapy administration play a crucial role in the development of acute or late myocardial dysfunction. Primary prevention initiatives cover a wide area that ranges from conventional heart failure drugs, such as β-blockers and renin-angiotensin-aldosterone system antagonists to nutritional supplementation and physical training. Additional studies on the pathophysiology and cellular mechanisms of anticancer-drug-related CTX will enable the introduction of novel therapies. We present various typologies of prevention strategies, describing the approaches that have already been used and those that could be effective on the basis of a better understanding of pharmacokinetic and pharmacodynamic CTX mechanisms.